Desenvolvimento e implementação de um sistema de monitoramento em tempo real da tensão da rede com acesso remoto - Colnago, Guilherme Piazentini (2009)
Some years ago in Brazil the power quality was related, basically, with interruption of supplied energy and certain special loads of industry. In recent years, however, under controls of the regulating agency ANEEL (Agência Nacional de Energia Elétrica) and with specialists, the power quality area received the due attention and was legislated and acquired regulations. So, finally, the area of Power Quality was formally created and now it embraces several electrical phenomena and events. Because of the new regulations, this work presents a project of a power quality meter. One of meter s focuses is to be a low cost system and becomes able to be used in large scale. This power quality meter is an electronic system that processes the voltage signal of electrical network and extracts data related to power quality; the data are locally stored and after they are remotely accessed and transmitted to a data base to be analyzed.